Upaya Meningkatkan Minat Belajar Sejarah Melalui Metode Belajar Bermain Peran (Role Playing) Siswa Kelas IX Pada Mata Pelajaran IPS SMP Swasta Sinar Pancasila Betun - Merlyn Marsalina Ndaong; Augusta De Jesus Magalhaes; Antonius Bere; Yuditha Sofiana Kofi (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This study aims to increase the interest in learning history among ninth-grade students at SMP Sinar Pancasila Betun through the application of the role-playing method. The research problem addressed in this study is how effective the role-playing method is in increasing students' interest in learning history and what factors influence the success of this method. The study uses a classroom action research (CAR) method, consisting of four cycles. Each cycle includes stages of planning, implementation, observation, and reflection. Data collection instruments used include observation sheets and learning interest questionnaires. The results of the study show a significant increase in students' interest in learning after the application of the role-playing method. In the second cycle, the average student learning interest was at 66%, and it gradually increased to 81% by the fourth cycle. The discussion of these results indicates that the role-playing method not only increases students' interest in learning but also facilitates collaboration, active participation, and student creativity in the history learning process. Therefore, it can be concluded that the role-playing method is effective in increasing the interest in learning history among ninth-grade students at SMP Sinar Pancasila Betun.